2020
DOI: 10.1002/hed.26312
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of fiberoptic laryngoscopy prior to total thyroidectomy for low‐risk thyroid cancer patients

Abstract: Background Flexible fiberoptic laryngoscopy is performed prior to thyroid surgery to evaluate the function of the recurrent laryngeal nerve. We assess the cost‐effectiveness of preoperative laryngoscopy prior to total thyroidectomy for a low‐risk thyroid cancer patient without dysphonia. Methods A decision tree analysis was performed from a third‐party payer perspective. We assessed the cost‐effectiveness of fiberoptic laryngoscopy prior to total thyroidectomy for T2N0M0 papillary thyroid carcinoma, such that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…A study published in 2020 conducted CUA for fiberoptic laryngoscopy prior to total thyroidectomy in low-risk thyroid cancer patients (T2N0M0 PTC) based on a decision model for 30 years ( Table 2 ) [ 29 ]. The study only considered direct costs, which were converted into 2019 direct costs according to public expense data (Medicare) and the literature with a 3% discount rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study published in 2020 conducted CUA for fiberoptic laryngoscopy prior to total thyroidectomy in low-risk thyroid cancer patients (T2N0M0 PTC) based on a decision model for 30 years ( Table 2 ) [ 29 ]. The study only considered direct costs, which were converted into 2019 direct costs according to public expense data (Medicare) and the literature with a 3% discount rate.…”
Section: Resultsmentioning
confidence: 99%
“…The first points to consider are direct, indirect, and intangible costs [21]. Most previous studies used direct costs, but some studies also used complication costs, the value of death, and indirect costs [26][27][28][29][30]. Previous thyroid cancer studies used discount rates of 3% to 6%, although there were variations across countries and research periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that vocal fold paralysis cannot always be determined based on voice symptoms. 20,21 Without preoperative laryngeal assessment there is no ability to differentiate preexisting vocal fold paralysis from vocal fold paralysis caused by VNS surgery. Recognizing vocal fold paralysis before VNS surgery would also be valuable for preoperative surgical planning and for discussing the risk of laryngeal complications with patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the value of reoperating was found to be difficult to determine without a preoperative evaluation. Studies have shown that vocal fold paralysis cannot always be determined based on voice symptoms . Without preoperative laryngeal assessment there is no ability to differentiate preexisting vocal fold paralysis from vocal fold paralysis caused by VNS surgery.…”
Section: Discussionmentioning
confidence: 99%